2015
DOI: 10.1016/j.bpj.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the Central Part of Tropomyosin Increases the Bending Stiffness of the Thin Filament

Abstract: A two-beam optical trap was used to measure the bending stiffness of F-actin and reconstructed thin filaments. A dumbbell was formed by a filament segment attached to two beads that were held in the two optical traps. One trap was static and held a bead used as a force transducer, whereas an acoustooptical deflector moved the beam holding the second bead, causing stretch of the dumbbell. The distance between the beads was measured using image analysis of micrographs. An exact solution to the problem of bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(59 reference statements)
3
11
1
6
Order By: Relevance
“… who also simulated the D137L construct with MD. Although these authors calculated the persistence length of the whole Tpm molecule bound to actin while we estimated it only for an isolated middle segment of unbound Tpm and therefore it was undiminished by such interaction, both calculations show an increase in stiffness caused by the D137L mutation consistent with experimental data . Moore et al .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“… who also simulated the D137L construct with MD. Although these authors calculated the persistence length of the whole Tpm molecule bound to actin while we estimated it only for an isolated middle segment of unbound Tpm and therefore it was undiminished by such interaction, both calculations show an increase in stiffness caused by the D137L mutation consistent with experimental data . Moore et al .…”
Section: Discussionsupporting
confidence: 81%
“…However, our single molecule experiments have not shown changes in the unitary force of myosin interaction with reconstructed thin filaments containing these Tpm constructs, which nevertheless strongly affected the cooperativity of the interaction in the in vitro motility assay . We therefore concluded that increase in force in the motility assay induced by these substitutions is caused by an involvement of additional myosin heads in the interaction due to global stabilization of the Tpm structure and global increase in stiffness of the Tpm strand . The M127A/I130A or M141A/Q144A substitutions increased Tpm stiffness only locally probably due to a closure of the interhelical gap (Table and Fig.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Replacement of these residues with canonical ones, D137L and G126R (9,10), was shown in solution studies to significantly increase coiled-coil stability and decrease molecular mobility or flexibility (9,(11)(12)(13). A significant decrease in the flexibility of reconstructed thin filaments with the combined D137L/G126R substitution was also shown by means of the two-bead optical trap technique (14).…”
Section: Introductionmentioning
confidence: 87%